Salmonella: Role in Internal and External Environments and Potential as a Therapeutic Tool - Patrick J. Naughton; Violetta R. Naughton; James S. G. Dooley (Applied Microbiology, 2024)
Salmonella has had a long and intimate relationship with humans and continues to raise concerns for human health, but this close bond also provides opportunities for new therapeutics and treatments. Although Salmonella enterica serovar Typhi is the principal organism that comes to mind in terms of death and morbidity, it is the non-typhoidal Salmonellae that have the most health and economic implications. The developed world has had a challenging relationship with Salmonella, particularly in the UK and the EC/EU, experiencing significant Salmonella outbreaks in the 1980s and 1990s. As a consequence, the research focus was on understanding the nature of infection in food animals and on developing ways and means of controlling zoonotic infections. This led to the development of numerous model systems for the study of Salmonella both in vitro and in vivo. The introduction of vaccination has all but eliminated Salmonella in eggs and reduced perceived risk held by the general public. At the same time as Salmonella in eggs was being brought under control in the UK and EU, the danger posed by antibiotic resistance was beginning to emerge. In the past, with the efficacy of antibiotics against Gram-negative bacteria being unchallenged, there was limited focus on the threat posed by antibiotic resistance in non-typhoidal Salmonella. However, the identification of Salmonella as the first ‘multidrug-resistant’ organism, the presence of invasive non-typhoidal Salmonella in North Africa and the emergence of monophasic Salmonella enterica serovar Typhimurium across Europe, Asia and the Americas have prompted renewed interest in Salmonella research, particularly in the context of non-infectious disease, biofilm studies and antibiotic resistance. At the same time, research has continued to develop ways of taking advantage of what Salmonella offers in the way of pathogenic factors and the therapeutic and treatment applications in areas such as vaccine development, cancer therapeutics and drug delivery and the role of Salmonella in non-infectious diseases supported by developments in molecular and genomic methods.